Photometric Calibration for the Beijing–Arizona Sky Survey and Mayall z-band Legacy Survey. (21st June 2018) - Zhou, Zhimin; Zhou, Xu; Zou, Hu; Zhang, Tianmeng; Nie, Jundan; Peng, Xiyan; Fan, Xiaohui; Jiang, Linhua; McGreer, Ian; Yang, Jinyi; Dey, Arjun; Ma, Jun; et al.
Abstract: We present the photometric calibration of the Beijing–Arizona Sky Survey and Mayall z -band Legacy Survey, which are two of the three wide-field optical legacy imaging surveys to provide the baseline targeting data for the Dark Energy Spectroscopic Instrument project. The method of our photometric calibration is subdivided into the external and internal processes. The former utilizes the point-source objects of Pan-STARRS1 survey (PS1) as the reference standards to achieve the zero points of the absolute flux for individual exposures. And then the latter revise the zero points to make them consistent across the survey based on multiple tilings and large offset overlaps. Our process achieves a homogeneous photometric calibration over most of the sky with precision better than 10 mmag for g and r bands, 15 mmag for z band. The accuracy of the calibration is better than 1% at the bright end (16–18 mag) over most of the survey area.